2020
DOI: 10.1155/2020/2132918
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sex Differences on Endothelial Function and Circulating Endothelial Progenitor Cells in Hypertriglyceridemia

Abstract: Background. Men have a higher risk and earlier onset of cardiovascular diseases compared with premenopausal women. Hypertriglyceridemia is an independent risk factor for the occurrence of ischemic heart disease. Endothelial dysfunction is related to the development of ischemic heart disease. Whether sex differences will affect the circulating endothelial progenitor cells (EPCs) and endothelial function in hypertriglyceridemia patients or not is not clear. Methods. Forty premenopausal women and forty age- and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Sexual dimorphism in ECs has been observed and provides insight into sex-based differences that may affect the risk of vascular diseases (Stanhewicz et al, 2018). Compared with men, premenopausal women with hypertriglyceridemia were found to have increased levels of progenitor ECs, along with enhanced production of nitric oxide required for vascular homeostasis, indicating a protective role for these ECs against vascular disease in women (Ren et al, 2020). Additionally, female cultured human umbilical ECs showed higher expression of genes involved in cell proliferation and migration than did male human umbilical ECs.…”
Section: Contribution Of Sex-based Differences To Ec Heterogeneitymentioning
confidence: 99%
“…Sexual dimorphism in ECs has been observed and provides insight into sex-based differences that may affect the risk of vascular diseases (Stanhewicz et al, 2018). Compared with men, premenopausal women with hypertriglyceridemia were found to have increased levels of progenitor ECs, along with enhanced production of nitric oxide required for vascular homeostasis, indicating a protective role for these ECs against vascular disease in women (Ren et al, 2020). Additionally, female cultured human umbilical ECs showed higher expression of genes involved in cell proliferation and migration than did male human umbilical ECs.…”
Section: Contribution Of Sex-based Differences To Ec Heterogeneitymentioning
confidence: 99%
“…Studies have shown that HDL increases the number and activity of EPCs ( 41 43 ). Various studies have shown that circulating EPCs are reduced in the presence of classic CVD risk factors ( 44 ), non-modifiable risk factors such as age and gender also affect the number of EPCs ( 45 ). Accordingly, it has been determined that older people have fewer CD34 + KDR + cells than younger people and men have fewer CD34 + KDR + cells than women.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it has been determined that older people have fewer CD34 + KDR + cells than younger people and men have fewer CD34 + KDR + cells than women. The number of EPCs may be a factor in explaining the protection of fertile women from CVD risk ( 45 ). It can be claimed that the risk of CVD is higher in people with a low EPC count because these people have impaired endothelial repair and compensatory angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertriglyceridemia has also been shown to negatively affect EPC biology. Hypertriglyceridemia leads to endothelial dysfunction and injury by interfering with SDF-1/CXCR-4 binding and NO pathways, thus affecting mobilization, migration, homing, and the vasculogenic properties of EPC [ 60 , 61 ].…”
Section: Endothelial Repair In Patients With Lipid Disordersmentioning
confidence: 99%